An Examination of Business Applications and Implications of Emerging Technologies - Yeganeh, Hamid (Journal of Comparative International Management)

(untitled) (Management Futures, 2021)
This paper aims at offering a review and assessment of various emerging technologies and their business applications and implications. The study focuses on nineteen emerging technologies categorized under five major themes: (1) automation and robotics; (2) data and connectivity; (3) interfaces and visualization; (4) materials; (5) energy and resources. For each theme, the associated technologies are examined, their business applications and implications are assessed, and some examples are provided. In the end, an integrative table of nineteen emerging technologies is offered, and some avenues for future research are discussed.